2017
DOI: 10.20315/asetl.113.1
|View full text |Cite
|
Sign up to set email alerts
|

Poslovno povezovanje lastnikov gozdov na primeru Društva lastnikov gozdov Pohorje-Kozjak

Abstract: IZVLEČEKVečina ključnih problemov gospodarjenja z zasebnimi gozdovi izhaja iz majhne in razdrobljene gozdne posesti, ki je v lasti velikega števila lastnikov. Zato je njihovo povezovanje ključno za bolj učinkovito gospodarjenje. Največji razmah so v zadnjih letih doživela društva lastnikov gozdov, ki so po Zakonu o društvih opredeljena kot samostojno in nepridobitno združenje. Kot odgovor temu se je med člani pokazala težnja po nadgradnji takšne oblike povezovanja v smeri poslovnega povezovanja. V prispevku je… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…While associations, cooperatives and agricultural commons might in some cases be non-market, forestry-based SI initiatives, the current social entrepreneurship policy framework is not favorable to their development. The forest policy framework supports cooperation among private forest owners by regulatory, informational, financial and networking instruments, but the problem of inactive private forest owners and their associations persists in Slovenia (Pezdevšek Malovrh and Laktić, 2017). Approximately 50% of private forest owners do not manage their forests and are not willing to join an association .…”
Section: What Are the Implications Of Slovenian Policy Framework Conditions For The Development Of Forestry-based Si Initiatives?mentioning
confidence: 99%
“…While associations, cooperatives and agricultural commons might in some cases be non-market, forestry-based SI initiatives, the current social entrepreneurship policy framework is not favorable to their development. The forest policy framework supports cooperation among private forest owners by regulatory, informational, financial and networking instruments, but the problem of inactive private forest owners and their associations persists in Slovenia (Pezdevšek Malovrh and Laktić, 2017). Approximately 50% of private forest owners do not manage their forests and are not willing to join an association .…”
Section: What Are the Implications Of Slovenian Policy Framework Conditions For The Development Of Forestry-based Si Initiatives?mentioning
confidence: 99%
“…Forest owners in all age groups managed their forests with similar intensity (20 m 3 /ha over a period of five years) [58]. Previous studies have also indicated that younger owners are more likely to consider selling timber [59] and are more interested in business integration [60].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed that forest owners with larger forest properties are more open to business cooperation [60] and the affinity for subsidies [71]. Furthermore, research among Slovenian private forest owners who actively managed their forests in the last five years showed that larger forest owners are more active in harvesting, and a higher percentage of them hire professional forestry contractors in comparison to smaller forest owners [58].…”
Section: + + +mentioning
confidence: 99%
“…Much research deals with cooperation between private forest owners (e.g. Fischer et al 2019, Górriz-Mifsud et al 2019, Pezdevšek Malovrh 2010, Pezdevšek Malovrh et al 2017, Põllumäe et al 2016, Rauch 2007) and mostly analyzes PFOAs with the aim of understanding the influence of various factors on the willingness of private forest owners to cooperate in PFOAs (Pezdevšek Malovrh et al 2010), the reasons for establishing PFOAs (Sarvašová et al 2015, Schraml 2005, factors that influenced the establishment, development, professionalism and efficiency of PFOAs (Černač and Pezdevšek Malovrh 2020, Fabra-Crespo and Rojas-Briales 2015, Glück et al 2010, Kronholm 2016, Leban 2014, Lönnstedt 2014, Pezdevšek Malovrh and Laktić 2017, Sarvašová et al 2015, the motives of private forest owners and their benefits for joining PFOA (Hrib et al 2018, Pezdevšek Malovrh et al 2011, Põllumäe et al 2014, the effects of PFOAs on forest management (Hansmann et al 2016, Seeland et al 2011, and the role of stakeholders (Aurenhammer 2017a, Aurenhammer et al 2017b, Šálka et al 2016. These studies provide important insights into the state of the art of PFOAs, but mainly focus on only one organizational form of cooperation.…”
Section: Introductionmentioning
confidence: 99%